Pengembangan Media Pembelajaran The Cow Farm Berbentuk Aplikasi “Momoci” untuk P5 Anak Usia 5-6 Tahun - Wahyuningtyas, Ani Agustin; Samawi, Ahmad; Anisa, Nur (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Learning media serves as an instructional aid in the teaching and learning process by clarifying the delivery of messages so that learning objectives can be achieved effectively. This study aims to develop an application-based learning media called Momoci, which contains animated videos and evaluation games with the theme The Cow Farm to improve early childhood knowledge regarding types of cows and their proper care, while also supporting the Pancasila Student Profile Strengthening Project (P5) for children aged 5–6 years. This study employed a Research and Development (R&D) method using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation), integrating both qualitative and quantitative approaches. The development process included needs analysis, application design, product development, implementation, and evaluation of media effectiveness. Validators were selected purposively based on their expertise and competence in learning media and early childhood education materials, involving two media experts, two material experts, and three early childhood education practitioners as user validators. The research sample consisted of 61 kindergarten Group B children aged 5–6 years from three early childhood education institutions, namely TK Negeri Pembina Wonosalam, Jombang Regency, TK Negeri Pembina Bareng, Jombang Regency, and Children Center Brawijaya Smart School, Malang. The findings revealed that The Cow Farm learning media in the form of the Momoci application was categorized as highly feasible based on media, material, and practitioner validation results. Product revisions were conducted according to recommendations from media and material experts, including adjustments to the display of the Pancasila Student Profile, the use of capital letters, improvements to the landscape layout, replacement of level names with character-based titles, and the addition of user guidelines. The implementation results indicated that the Momoci application was effective as an interactive learning medium for children aged 5–6 years..